Monsters and monarchs: serial killers in classical myth and history - Felton, Debbie (University of Texas Press, 2021)
Introduction. Serial killers in the ancient world -- Identifying serial killers then and now -- Methods to the madness -- What motivates serial killers across the ages -- Murderous Greek roof-tiles and other legal problems -- Murder and the advantages of roman citizenship -- The popularity of serial poisoning -- Heracles and the headhunters -- Theseus and the highway killers -- How boxing moved from serial murder to Olympic sport -- Serial murders in local legends -- Serial slaying of suitors and spouses -- Witches and other child-murderers -- Serial murder then and now, there and here